LA REPRESENTATION SOCIALE Un concept au carrefour de la psychologie sociale et de la sociologie - KOUIRA, Aicha (Journal of Human Sciences, 2014)
A great number of students in social human sciences direct their researches towards different aspects of socials representations. This article is due to a series of meeting, elaborated and written by three research teachers, their aim in to allow these student to understand, and deeper the different theorical approaches, including the methodological and social representation, their fields, their articulations, their belief system, the theory from the central nucleus, it’s peripheric elements, it’s effective dimension.